Beberapa Metode pada Masalah Pemrograman Stokastik - Ihda Hasbiyati; Hasriati Hasriati (Mathematics Department, Faculty of Science and Technology, UIN Sunan Ampel Surabaya, 2017)
Stochastic programming problem is mathematical problem (linear, integer, mixed integer, and nonlinier) with stochastic element lies data. To get reasonable solution and optimal with its stochastic data is needed several method. Applicable method in trouble stochastic programming are L-Shape decomposition and lagrange decomposition. Each method can determine optimal solution to troubleshoots stochastic programming